Prevalence of age‐related macular degeneration in Chinese populations worldwide: A systematic review and meta‐analysis. (22nd July 2019) - Jin, Guangming; Zou, Minjie; Chen, Aiming; Zhang, Yichi; Young, Charlotte A.; Wang, Shi‐Bin; Zheng, Danying
Abstract: Importance: Age‐related macular degeneration (AMD) is a leading cause of irreversible blindness, but the magnitude of AMD among Chinese populations worldwide is still unknown. Background: To investigate the prevalence of AMD in Chinese populations worldwide. Design: Meta‐analysis. Participants: Nine studies with 29 344 subjects in total. Methods: All population‐based studies on AMD prevalence in Chinese populations worldwide were identified and only studies using standardized AMD grading systems (Wisconsin Age‐Related Maculopathy Grading System, Age‐Related Eye Disease Study System of Classifying AMD, the International Classification and Grading System for AMD or the Clinical Classification of Age‐Related Macular Degeneration) were included. We used meta‐analysis to estimate the pooled prevalence and its 95% confidence interval (95% CI) of AMD, and to explore the racial differences and regional differences. Main Outcome Measures: Age‐specific prevalence, gender‐specific prevalence and pooled prevalence of early and late AMD among Chinese population worldwide. Results: Altogether, 9 studies with 29 344 individuals were included and analysed. The crude pooled prevalence of early and late AMD among Chinese populations worldwide aged 50 years and above is 4.9% (95% CI: 3.1%‐7.7%) and 0.7% (95% CI: 0.5%‐1.1%), respectively. Corresponding crude prevalence among Caucasian populations are 10.1% (95% CI: 5.7%‐17.2%) and 1.6% (95% CI: 1.0%‐2.4%). There are statistically significant differences within age and gender subgroups. Conclusions and Relevance: Among persons aged 50+ years, both early AMD and late AMD in Chinese populations worldwide were less common compared with that reported from Caucasian populations. Considering the significant racial or ethnic differences in AMD prevalence between Chinese and Caucasian people, further studies are needed to explore the possible mechanism behind this discrepancy.